OP0175 Characterization of novel stromal-derived autoantigens recognized by ra synovial monoclonal antibodies. (15th June 2017) - Corsiero, E; Jagemann, L; Prediletto, E; Pitzalis, C; Bombardieri, M
Abstract : Background: We previously showed that up to 40% of RA synovial recombinant monoclonal antibodies (RA-rmAbs) generated from germinal center-like structure (GC-LS+) RA synovium recognize citrullinated antigens contained in neutrophils extracellular traps (NET) (1). The cellular source of other potential autoantigens targeted by the majority of locally differentiated B cells remains undefined. Recently, RA-fibroblast-like synoviocytes (RA-FLS) have been implicated in the release of citrullinated antigens (2, 3). However, whether these cells are targeted by RA-rmAbs is still unknown. Objectives: Here, we aimed to define the RA-rmAbs immunoreactivity towards i) RA-FLS and ii) identify potential stromal-derived autoantigens. Methods: 67 RA-rmAbs were generated from single CD19+ B cells FACS-sorted from fresh synovial cell suspensions following IgVH +VL genes cloning (1). RA-rmAbs were tested by means of i) cell-based immunofluorescence assays with FLS of RA patients and controls (osteoarthritis (OA)-FLS and RA-dermal fibroblast (RA-DF)), ii) co-localization with stromal specific markers and iii) immunoenzymatic tests with co-localizing antigens. Control rmAbs were also used (Sjögren's syndrome/healthy donor-IgG rmAbs). Results: Immunofluorescence on RA-FLS demonstrated reactivity of 21% of RA-rmAbs (14/67 rmAbs) towards cytoplasmic components of FLS. Only 4 rmAbs out of 14 were binding both FLS and NET components. For some rmAbs this reactivity was not specific to RA-FLS since it was also observed for OA-FLS and RA-DF. Interestingly, strong co-localization was observed with calreticulin (CRT) which in its citrullinated (cit-CRT) form has been previously shown to recognize the RA "shared epitope" HLA domain sequence (3). When tested in ELISA for native vs cit-CRT, 57% (8/14 rmAbs) of the FLS-reactive RA clones showed binding to CRT with 4 out of 8 rmAbs displaying increased immunoreactivity towards cit-CRT. Controls rmAbs showed no reactivity to either FLS or CRT. Preliminary data suggest that RA patient serum preferentially recognize the lectin-like N-terminal domain of CRT (4). Conclusions: Here, we provide novel evidence that a subset of locally differentiated B cells within RA synovial GC-LS can react towards RA-FLS derived antigens. Preliminary data suggest that part of this reactivity is directed towards CRT. Identification of immunodominant epitopes within CRT is under investigations. References: Corsiero et al, ARD 2015. Sorice et al, Rheumatology 2016. Ling et al, AR 2013. Hong et al, JI 2010. Disclosure of Interest: None declared